The Game of Anchors : Studying the Causes of Currency Crises in Belarus - Miksjuk, Alex (IMF Working Papers; Working Paper ;, 2015)
Belarus experienced a sequence of currency crises during 2009-2014. Our empirical results, based on a structural econometric model, suggest that the activist wage policy and extensive state program lending (SPL) conflicted with the tightly managed exchange rate regime and suppressed monetary policy transmission. This created conditions for the unusually frequent crises. At the current juncture, refocusing monetary policy from exchange rate to inflation would help to avoid disorderly external adjustments. The government should abandon wage targets and phase out SPL to remove the underlying source of the imbalances and ensure lasting stabilization.